Circular sensing networks for guided waves based structural health monitoring. (January 2016) - Wandowski, T.; Malinowski, P.H.; Ostachowicz, W.M.
Abstract: In this paper, results of damage localization performed for four sensing network configurations are compared. Process of damage localization is based on guided waves propagation phenomenon. Guided waves are excited using piezoelectric transducer and received by scanning laser vibrometer. Different excitation frequencies are also investigated. In experimental investigations two types of piezoelectric transducers are used as guided waves exciters. Frequency–magnitude characteristics of symmetric and antisymmetric modes are created for both types of transducers. These characteristics allow a choice of an excitation frequency for efficient generation of selected wave mode. The amplitude of second mode in this case has negligibly small value. Finally, sensing networks in the form of circle with three different diameters are realized based on piezoelectric transducers. Damage localization algorithm is prepared in MATLAB ® environment as well as in C++. Highlights: Investigation of wave excitability by two types of piezoelectric sensors. Investigated of the directional characteristics of the circular networks. Introduction of new relative damage index taking into account the boundary reflection. The influence of number of sensing points on damage index value.